Judicial-Administrative Cases Arising from the Relations of State Control (Supervision): Concept, Types, Problems and Prospects of Administrative-Procedural Regulation - A. I. Stakhov (Сибирское юридическое обозрение, 2018)
The article on the basis of a comprehensive analysis of the modern administrative procedure legislation of the Russian Federation developed the concept of judicial-administrative cases arising from the relations of state control (supervision). The typical types (categories) of judicial-dministrative cases arising from the relations of state control (supervision) and considered by the courts of general jurisdiction, arbitration courts are identified. A proposal was made to develop a special Plenum of the Supreme Court of the Russian Federation, as well as measures to systematize and optimize the procedures of administrative proceedings, aimed at eliminating the uncertainties and conflicts of administrative and procedural regulation of judicial resolution of cases arising from the relations of state control (supervision). are identified. A proposal was made to develop a special Plenum of the Supreme Court of the Russian Federation, as well as measures to systematize and optimize the procedures of administrative proceedings, aimed at eliminating the uncertainties and conflicts of administrative and procedural regulation of judicial resolution of cases arising from the relations of state control (supervision).